TANTANGAN DAN PELUANG IMPLEMENTASI KEBIJAKAN PENDIDIKAN: STUDI KASUS IMPLEMENTASI KEBIJAKAN PENDIDIKAN DI SD NEGERI MUNCAN KABUPATEN LOMBOK TENGAH - Evi Zuyyina; Nurhasanah; Donita Filiyanti N.; Basilius Redan Werang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of education policy at SD Negeri Muncan, Central Lombok Regency, identify the challenges and opportunities encountered, and formulate strategies to improve its effectiveness. This research employed a qualitative approach using a case study method. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. Data credibility was ensured through source triangulation, technique triangulation, and member checking. The findings indicate that the implementation of educational policies, including the National Curriculum, learning assessment, character education, school digitalization, teacher professional development, and school-based management, has been carried out in accordance with government policy directions. The effectiveness of policy implementation is influenced by communication, resource availability, implementers' commitment, and a well-defined bureaucratic structure. The main challenges include disparities in teacher competence, limited facilities, administrative workload, frequent policy changes, and varying levels of parental involvement. Conversely, participatory school leadership, teachers' commitment, community support, collaborative school culture, and the use of information technology provide significant opportunities to enhance educational quality. The study highlights the importance of strengthening human resource capacity, stakeholder collaboration, and continuous evaluation to improve the effectiveness of education policy implementation at the elementary school level.